Sustainability assessment of date and pistachio agricultural systems using energy, emergy and economic approaches. (20th August 2018) - Jafari, Mahdi; Asgharipour, Mohammad Reza; Ramroudi, Mahmoud; Galavi, Mohammad; Hadarbadi, Gholamreza
Abstract: Nehbandan is one of the date producing regions in Iran; however, within the last 20 years, date production has been substituted by pistachio production. To analyze the reasons behind this conversion, the productivity and sustainability of date and pistachio production systems are examined using energy, emergy and economic techniques. Total emergy supporting the systems was estimated to 2.26E+16 and 2.97E+16 sej ha −1 yr −1 for the date and pistachio production systems, respectively. The purchased nonrenewable resource accounts for 58.4% and 59.4% of total emergy flow for the date and pistachio production, respectively. This shows that both studied systems are an extremely open system influenced strongly by inputs purchased from economy. The compositions of purchased emergy inputs for both date and pistachio systems are similar to a great extent. Manure and phosphorus fertilizer have the highest contributions to emergy inputs, respectively. Economic analyses indicate that the output/input ratio and the net profit in pistachio production are higher than that of date. As a general outcome, the higher economic income from pistachio production is the reason for orienting from date production systems to pistachio production. However, energy and emergy assessments indicate that date production is more sustainable in the long term. The emergy, energy and economic techniques are different but complement each other; each considering a specific aspect of one system. A combined use of these techniques not only shows the reasons behind the current status of systems but also provides methods to adjust them towards a more sustainable status. Highlights: Input emergy for pistachio systems is about 32% higher than date systems. The compositions of purchased emergy inputs for both systems are similar. Higher environmental performance of a system leads to a lower economic performance. The date systems are more sustainable than pistachio systems in the long term.